Overproduction of Chromosomal ampC β-Lactamase Gene Maintains Resistance to Cefazolin in Escherichia coli Isolates - Masato Kawamura; Ryota Ito; Yurina Tamura; Mio Takahashi; Miho Umenai; Yuriko Chiba; Takumi Sato; Shigeru Fujimura (Microbiology Spectrum, 2022)
ABSTRACT Cefazolin, an active in vitro agent against Escherichia coli, is used to treat urinary and biliary tract infections. Cefazolin is used widely as an antibiotic, and the increase in the emergence of cefazolin-resistant E. coli in many countries is a major concern. We investigated the changes in the susceptibility of E. coli clinical isolates to cefazolin following exposure. A total of 88.9% (16/18 strains) of the strains acquired resistance to cefazolin. All strains with an MIC to cefazolin of 2 μg/mL became resistant. The expression of chromosomal ampC (c-ampC) increased up to 209.1-fold in the resistant strains. Moreover, 11 of the 16 E. coli strains (68.8%) that acquired cefazolin resistance maintained the resistant phenotype after subculture in cefazolin-free medium. Therefore, the acquisition and maintenance of cefazolin resistance in E. coli strains were associated with the overexpression of c-ampC. Mutations in the c-ampC attenuator regions are likely to be maintained and are one of the key factors contributing to the increase in the number of cefazolin-resistant E. coli worldwide. IMPORTANCE This study is the first to demonstrate that mutations in the chromosomal-ampC attenuator region are responsible for the emergence of cefazolin resistance in Escherichia coli strains. The resistance was maintained even after culturing E. coli without cefazolin. This study highlights one of the key factors contributing to the increase in the number of cefazolin-resistant E. coli strains, which can pose a considerable challenge for treating common infections, such as urinary tract infections.